A Critique of the Scientific Nature of Literary Research Based on the Critical Evaluation of Books on the Methodology of Research in Persian Literature - Ghodsieh Rezvanian; Haleh Kiani Barforushi (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The research method is one of the most important requirements of a scientific and academic research, and books published in the context of the research method can help researchers in understanding new and applied methods of research. The field of literature is one of the disciplines of the humanities, and the need to keep pace with the developments in the humanities in this field should be taken seriously.In this paper, while explaining the evolution of methodology in the humanities, the critical evaluation of 10 books in the field of Persian literature has been studied. The results of this research show that in the part of the literature research books, the traditional conception of research and the concepts of positivism about the nature of science and research are seen. The methodology presented in another part of the books is "an interpretative method"; most of these books have not addressed a critical methodology, and in some cases even critical theories are presented in an uncritical and interpretive nature. Two books out of the ten books reviewed in this study have explored the method of research with a critical approach in literature and have considered the need for critical thinking in different stages of literary research. Part of the traditional and uncritical concepts in these books is rooted in hegemony that defines literature as a tool for teaching and critique of the difficulty of literary works and tasty categories.